Post military life the adjustments and psychological well-being of retired military men in Puerto Princessa, Palawan. - Delos Santos, Gabrielle August N.
This study was conducted to identify the adjustments undergone by retired military men during their transitional from military life to civilian life, as well as their psychological well-being. Thirty (30) retired military men from Kalikasan Mutual Homes Brgy. San Pedro, Puerto Princesa, Palawan responded to the interview schedule administered by the researchers. Results showed that the retired military men did not have a difficulty in adjusting to the civilian life. They engaged themselves in social activities such as interacting within the neighborhood, meeting with their organizations, and maintaining healthy lifestyle for their social adjustment. Whereas for their personal adjustment, they engaged themselves in helping with household chores, and bond more with their family members to make time with the loss time that they had. However, with regards to their psychological well-being, they may have scored high per dimension, but their average mean scores meant otherwise where it belonged to the lowest quartile. Among the dimensions, it was positive relations that scored the highest. With the personal and social adjustments, and as well as the psychological well-being of the retired military men, it shows on what ways they were able to adjust while transitioning from military life to civilian life.